Microsatellite Loci Reveal High Genetic Diversity, Mutation, and Migration Rates as Invasion Drivers of Callery Pear (Pyrus calleryana) in the Southeastern United States - Sapkota, Shiwani; Boggess, Sarah L.; Trigiano, Robert N.; Klingeman, William E.; Hadziabdic, Denita; Coyle, David R.; Nowicki, Marcin (Frontiers in Genetics, 2022)
Pyrus calleryana Decne. (Callery pear) is a deciduous tree native to China, Japan, Korea, and Taiwan. It is a popular ornamental tree in the United States (US) with early spring blooms and vibrant fall color. There are at least 26 cultivars of P. calleryana available in the US of which “Bradford” is the most well-known. Open-pollinated P. calleryana escapees are becoming one of the most common invasive tree species in the eastern United States. Developing better management practices for invasive P. calleryana requires detailed knowledge about reproductive biology and genetic diversity of the species, however, little is currently known about genetic variability within those open-pollinated populations. We investigated genetic diversity and population structure of non-cultivated, escaped P. calleryana populations within a ∼177 km radius in the southeastern United States. Because P. calleryana exhibits a range of morphological variation with great evolutionary potential, we hypothesized that a high genetic diversity would be manifested among escaped P. calleryana. Using 15 previously developed microsatellite loci, we genotyped 180 open-pollinated P. calleryana individuals that were collected across six naturally occurring sites in Tennessee, Georgia, and South Carolina, United States. Our results demonstrated the presence of a population structure with high genetic diversity, high gene flow, and high genetic differentiation between individuals across collection sites. Our results revealed that P. calleryana populations had differentiated shortly after the introduction to the US, most likely from specimens imported from Asia, consistent with historical records and our prior findings. The high invasive potential of the species is perhaps best underscored by transformation of P. calleryana specimens introduced from Asia into escape populations at continental scale across the United States. Our data also provided novel insight into potential issues that could be problematic for the future as P. calleryana may pose a potential threat to the economy, ecology, and native biodiversity in invaded areas.